1995
DOI: 10.1099/0022-1317-76-12-3229
|View full text |Cite
|
Sign up to set email alerts
|

Replication slippage in the evolution of potyviruses

Abstract: Recently published evidence for sequence repetition in potyvirus genomes prompted us to analyse the published complete genome sequences and coat protein gene sequences of viruses of this family for evidence of replication slippage. Five of nine complete genomic sequences and 17 of 3 2 coat protein genes had significant sequence repetitions. Most of these were in coat protein genes, although the 5' region of the turnip mosaic virus genome also showed evidence of slippage. The results suggest that replication sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These regions often exist in intrinsically disordered domains together with ordered domains in the same proteins and are, most of the time, involved in regulatory functions [ 4 , 5 ]. The CB regions are found in all the three domains of life (Bacteria, Archaea and Eukarya) [ 6 – 9 ] and has also been reported in viral genomes [ 10 ]. Ekman et al [ 11 ] reported that CB are contained in highly connected “hub” proteins compared to non-hub proteins.…”
Section: Introductionmentioning
confidence: 99%
“…These regions often exist in intrinsically disordered domains together with ordered domains in the same proteins and are, most of the time, involved in regulatory functions [ 4 , 5 ]. The CB regions are found in all the three domains of life (Bacteria, Archaea and Eukarya) [ 6 – 9 ] and has also been reported in viral genomes [ 10 ]. Ekman et al [ 11 ] reported that CB are contained in highly connected “hub” proteins compared to non-hub proteins.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence there is a relatively high rate of misincorporation error, typically 0.1–10 mutations per 10 kb molecule per replication cycle (Domingo and Holland, 1997). In addition, replication slippage in the 5′ region of the TuMV genome has been described (Hancock et al ., 1995). The ability of TuMV to evolve rapidly may be the reason why it is able to infect a very broad range of hosts.…”
Section: Tumv Diversitymentioning
confidence: 99%
“…TAV RNA 3, as well as RNA 3B, contains two tandem repeats of 163 nt, suggesting an association with replication slippage (Hancock et al, 1995). Although internal in these tandem repeats of RNA 3, a single nucleotide difference in two repeats, A"*'' and G#"#* (Fig.…”
Section: Faimentioning
confidence: 99%